Studi Komparasi Model Project Based Learning dan Problem Based Learning terhadap Kemampuan Berpikir Kritis dengan Kemampuan Metakognitif sebagai Variabel Moderasi - Wahyu Juwita Permata Sari; Fitra Dila Lestari; Suparno Suparno (Educational Journal, 2026)
This study analyzes differences in students' critical thinking skills between those taught with Project Based Learning (PjBL) and Problem Based Learning (PBL) models, and examines the moderating role of metacognitive ability in this relationship. The research was motivated by persistently low critical thinking skills among students in Economics subjects and the need to compare constructivism-based learning models while considering students' metacognitive characteristics. Using a quantitative approach with a quasi-experimental design (Pretest-Posttest Non-Equivalent Group Design), the study involved 71 tenth-grade students from SMA Negeri 58 Jakarta selected through purposive sampling: class X-A as the PjBL group (36 students) and class X-C as the PBL group (35 students). Data were collected through a critical thinking skills test and a metacognitive ability questionnaire, then analyzed using N-Gain and Two-Way ANOVA tests with SPSS. Results revealed a significant difference in critical thinking skills between the two groups, with PBL proving more effective (moderate N-Gain category) than PjBL (low N-Gain category). Metacognitive ability showed no significant effect and did not significantly moderate the relationship between learning models and critical thinking skills, indicating consistent effects across metacognitive levels. These findings suggest that critical thinking skills in Economics can be optimized through broader implementation of PBL, regardless of students' metacognitive ability, contributing to constructivist learning research and informing effective teaching strategies.